Longitudinal changes in an autonomously functioning thyroid nodule with coexisting follicular thyroid carcinoma over 14 years. Issue 4 (19th April 2022) - Uchida, Taisuke; Yamaguchi, Hideki; Kawabata, Takayuki; Tanaka, Hiroyuki; Kawano, Fumiaki; Shimoda, Kazuya
Abstract: We present a female patient with autonomously functioning thyroid nodule (AFTN) and coexisting follicular thyroid carcinoma (FTC). At age 21, a left thyroid nodule was incidentally detected on computer tomography (CT) scan. At age 33, she had cervical compression and CT showed the left thyroid nodule had increased in size from 13 to 27 mm. Laboratory investigation showed subclinical hyperthyroidism with positive for anti-thyroid peroxidase antibody and normal level of serum thyroglobulin. Repeated fine needle aspiration cytology diagnosed with follicular neoplasm with Hashimoto's thyroiditis. At age 35, she presented with palpitations due to overt hyperthyroidism. The left thyroid nodule increased in diameter to 33 mm, and thyroid scintigraphy showed elevated uptake in the left thyroid nodule, indicating an AFTN. Thyroidectomy was performed, and the left thyroid nodule was pathologically diagnosed with FTC with capsular invasion. In this case, the longitudinal increase in AFTN size suggested FTC and led to thyroidectomy.